2021
DOI: 10.3390/jcm10215141
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Impact of New-Onset Atrial Fibrillation on Long-Term Risk of Ischemic Stroke after Acute Myocardial Infarction

Abstract: Background: Atrial fibrillation (AF) has been identified as a major risk factor for mortality after acute coronary syndrome (ACS). However, the long-term risk of ischemic stroke associated with new-onset atrial fibrillation (NOAF) in ACS remains controversial, and its gender-specific association is unknown. Methods: We analyzed the data of 10,137 ACS survivors included in a multicenter, prospective registry for Korean patients with acute myocardial infarction (AMI) between January 2004 and August 2014. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…22,23 A study by Fu et al 24 suggested that older people are more likely to develop NOAF after AMI occurrence. Other studies [25][26][27] have reported similar conclusions.…”
supporting
confidence: 75%
“…22,23 A study by Fu et al 24 suggested that older people are more likely to develop NOAF after AMI occurrence. Other studies [25][26][27] have reported similar conclusions.…”
supporting
confidence: 75%